Dual‐Additive Assisted Chemical Vapor Deposition for the Growth of Mn‐Doped 2D MoS2 with Tunable Electronic Properties. Issue 15 (2nd October 2019) - Cai, Zhengyang; Shen, Tianze; Zhu, Qi; Feng, Simin; Yu, Qiangmin; Liu, Jiaman; Tang, Lei; Zhao, Yue; Wang, Jiangwei; Liu, Bilu; Cheng, Hui‐Ming
Abstract: Doping of bulk silicon and III–V materials has paved the foundation of the current semiconductor industry. Controlled doping of 2D semiconductors, which can also be used to tune their bandgap and type of carrier thus changing their electronic, optical, and catalytic properties, remains challenging. Here the substitutional doping of nonlike element dopant (Mn) at the Mo sites of 2D MoS2 is reported to tune its electronic and catalytic properties. The key for the successful incorporation of Mn into the MoS2 lattice stems from the development of a new growth technology called dual‐additive chemical vapor deposition. First, the addition of a MnO2 additive to the MoS2 growth process reshapes the morphology and increases lateral size of Mn‐doped MoS2 . Second, a NaCl additive helps in promoting the substitutional doping and increases the concentration of Mn dopant to 1.7 at%. Because Mn has more valance electrons than Mo, its doping into MoS2 shifts the Fermi level toward the conduction band, resulting in improved electrical contact in field effect transistors. Mn doping also increases the hydrogen evolution activity of MoS2 electrocatalysts. This work provides a growth method for doping nonlike elements into 2D MoS2 and potentially many other 2D materials to modify their properties. Abstract : A dual‐additive chemical vapor deposition method achieves the growth of large lateral size 2D MoS2 substitutionally doped with Mn. The doping of Mn on the Mo sites in MoS2 is confirmed by scanning transmission electron microscopy imaging and various spectroscopic characterizations. As a result, the Mn‐doped MoS2 exhibits improved electrical contact and better hydrogen evolution reaction activity.